Inflammatory bowel disease-like colitis in a young Turkish child with glycogen storage disease type 1b and elevated platelet count - Saltik-Temizel, Inci Nur; Koçak, Nurten; Ozen, Hasan; Yüce, Aysel; Gürakan, Figen; Demir, Hülya (The Turkish Journal of Pediatrics, 2005)
Inflammatory bowel disease (IBD)-like colitis is a known entity in glycogen storage disease (GSD) type 1b patients. The mean age of the reported cases with IBD-like colitis was 12 +/- 5 years, and all had absolute neutrophil count (ANC) less than 1,000 cells/microl. We report a three-year-old girl with GSD type 1b that was dignosed by mutation analysis. The patient was hospitalized with fever, diarrhea, and perioral and anal ulcers. Colonoscopy was performed and IBD-like colitis was diagnosed. The patient had elevated platelet count beyond the age of three months, but IBD-like colitis was diagnosed at three years of age. An elevated platelet count may be a warning sign for the IBD-like colitis in young patients with GSD type 1b.